Leadership Rhetoric in Public Communication of the Regent of Sumbawa for the 2021-2024 Leadership Period - Rashikhah Marjannah; Abyzar Aggasi; Lalu Ahmad Taubih (CV. Abhinaya Indo Group, 2025)
This research aims to analyse the form and effectiveness of leadership rhetoric in the public communication of the Regent of Sumbawa, Drs. H. Mahmud Abdullah, especially in delivering Mo-Novi's flagship programmes in the 2021-2024 leadership period. Using a descriptive qualitative approach and case study method, this research refers to classical rhetoric theory (ethos, pathos, logos) as well as public communication theory according to Denis McQuail. Data were collected through in-depth interviews and documentation. The results show that the ethos aspect is quite strong formally, especially in terms of bureaucratic credibility and direct involvement of the leader. However, symbolic and emotional approaches that can strengthen public trust have not been optimally utilised. The pathos and logos aspects have also not been fully effective, because the communication patterns used still tend to be one-way, technocratic, and less in accordance with the socio-cultural characteristics of local communities. These findings indicate the importance of strengthening public communication strategies that are more adaptive, dialogic, and oriented towards emotional approaches so that leadership rhetoric can increase public understanding and participation in regional policies.